Arabic Curriculum Design for Non-Native Speakers in Multicultural Settings: A Systematic Literature Review - Hasyim Asy'ari; Khoiril Akhbar; Elok Rufaiqoh; Nahla Ibrahim ElJack Ibrahim; Sulfiatin Sulfiatin; Faruq Abdul Muid (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This article examines the challenges and directions of Arabic language curriculum development for non-Arabic speakers in a multicultural context through a PRISMA-based Systematic Literature Review of 12 Scopus articles. The results indicate challenges not only in the formal structure of the curriculum, but also in the weak connection between policies, pedagogical practices, teaching materials, evaluation, and learner needs. The existing curriculum is still normative, monocultural, less representative of minorities, not yet sensitive to multilingual identities, and has not responded to digital space and social change. Bibliometric analysis shows that studies are dominated by Western and European contexts with a global comparative perspective. Curriculum development needs to be directed towards an adaptive model that is flexible and integrated with technology, inclusive that recognizes diverse identities, and contextualized and connected to students' real experiences to be relevant and effective in a multicultural society.